Substrate integrated waveguide circular cavity with probe excitation / Siti Aminah Nordin - Nordin, Siti Aminah (2022)
A new substrate integrated waveguide circular cavity (SIWCC) band-pass filter with probe excitation has been designed and developed, which in C-Band frequency range that has potential applications in satellites and wireless communication systems. Some SIW structures suffer additional loss and are incompatible with smaller devices. Three different configurations of SIWCC cavity filters are proposed to contribute to tuning ability, low losses, and compact size. The first configuration consists of a SIWCC resonator interconnected with a triangle probe at both input and output ports. The design exhibits single-mode resonance in the passband, which operates at TM110 mode propagation. In the second configuration, to further investigate the performance of the SIWCC design, a rectangular perturbation slot was attached with the circular structure at both sides on the top layer. The design contributes towards an improvement in the electrical characteristic’s performance. Furthermore, the third configuration involved in the SIWCC design was tuned by perturbing via a hole connected to the cavities on the top metallic layer of SIW. This led to the advantage of simplicity in the design synthesising the SIWCC was applicable. Based on the low-pass equivalent network and low-pass prototype, the transformation from the equivalent circuit to the band-pass equivalent circuit was done. This allows the electrical characteristics controls for the resonator at the operating frequencies and the integration of the addition cavity into the initial design topology for the higher-order band-pass filter. As a result, cascading two circular cavities in the design exhibit dual-mode resonance frequency and excite at TM110 mode with more selective performance, compact, smaller devices size realization, and good electrical response. The design with a double layer printed circuit board (PCB) was fabricated using Rogers RO4350B™ substrates to achieve a multi layer structure in the coupling between the vertically coupled SIW cavity resonator. Finally, the simulations and experimental results in planar technology are also presented using an Ansoft High-Frequency Structure Simulator (HFSS) simulator to validate the proposed design of the filters at various configurations. It operates at frequencies 3.75 GHz and 4.75 GHz with fractional bandwidth (FBW) greater than 0.1 GHz, and average performance with insertion loss (IL) being less than 2 dB.